Trade-off between Efficiency and Equity on the Rationing in Health Insurance System: the Burden on the Poor - Manal Etemadi; Hasan Abolghasem Gorji (Shahid Sadoughi University of Medical Sciences, 2019)
Background: Nearly all of the rationing mechanisms have negative impacts on the poor. If the fair service access is not set as the top priority in the rationing choices, the poor will experience service limitation and scarcity. This study aims at investigating the effects of rationing policies on the poor covered by Iran Health Insurance System. Methods: This article is based on a qualitative study conducted in 2017. In total, 32 experts of health system financing participated in the study. A purposeful sampling method was applied till reaching knowledge saturation. Data were collected using semi-structured interviews. Afterwards, data was analyzed by framework analysis based on Bennet and Gilson pro-poor health financing system framework using MAXQDA10 software. Results: The main challenge of rationing through the insurance system in Iran is the rationing only for the poor. As a result of rationing decisions, the poor are mostly the first group affected by service limitation only because they exempted from paying the premium. The current implicit or explicit health services rationing policies in each dimension has jeopardized the access of the poor to the services. Conclusion: Every resource allocation and negotiation of service purchaser on the budgets should be aligned with the focus on vulnerable groups and their needs. The access of deprived groups should not be reduced for limited budgets or income prioritization. Every decision about the constraints on the usage of the services should be accompanied by the analysis of potential effects on the poor and preventive policies should be implemented so that the burden of service rationing could not be imposed on the poor